PENGGUNAAN METODE LIMA MENGAPA UNTUK MENGIDENTIFIKASI AKAR PENYEBAB CACAT PERMUKAAN BENDA KERJA PROSES PEMESINAN GERINDA DATAR: STUDI KASUS - Izdihar Hirzani; Arya Danutirta; Feriadi, Indra; Yudo, Eko (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Surface defects of the workpiece and the emergence of sparks that suddenly enlarge during the flat grinding process cause a decrease in product quality and create unsafe working conditions. This study aims to identify the causes of surface defects of the workpiece on a flat grinding machine in the Polmanbabel advanced machining laboratory. Identification of the cause of damage using the five why analysis method. The study was preceded by defining the problem and then asking the question "why" to the problem and for each answer given approximately five times. To help answer each "why" question, an analysis of the system's working mechanism and a physical examination of the parts or components connected to the Wheelhead were carried out. The results of the study found that the root cause of the occurrence of defects on the surface of the workpiece and the phenomenon of sparks that sometimes enlarge suddenly and during the grinding process of the flat grinding machine was the destruction of the rubber components of the motor and spindle clutch. This case study also proves that the five’s why method can effectively identify the root cause of damage to the flat grinding machine.